(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
This research compares business group-affiliated enterprises with independent firms on theNational Stock Exchange (NSE) in India from 1995 to 2022 and analyses the factors that influence two keydividend policy decisions. Linked businesses are bigger, more lucrative, and better leveraged than thenon-associated businesses. Based on the data, it seems that related businesses make different dividendpolicy choices than non-associated businesses. Dividend income is subject to taxation in India under theumbrella of other sources since the passage of the Income Tax Act, 1961. There has been a lot ofupheaval in how dividend income is taxed because of all the changes that have been made over theyears. Dividends are now taxed differently. U.S.-based firms that paid dividends to their shareholders,either recently or in the prior year, were also subject to a dividend distribution tax. However, after thedistribution, the recipient’s shares are once again taxable. Dividend recipients and the companies thatpay them would have been severely impacted by this action. This study analyses the tax consequencesfor owners of domestic equity shares of firms paying dividends from 1997 through 2022. Stock or mutualfund shares are used to provide dividends to shareholders. There are dividends paid out on a largeportion of their stock and mutual fund holdings. That’s why many of you are anxious about having to paytaxes on your investment gains. Therefore, we need to learn more about how dividends are taxed. Whena corporation pays out a significant portion of its profits to its shareholders on a consistent basis, itsstock is considered a dividend stock. Huge, profitable corporations sometimes attempt declaring largedividends when they anticipate their stock prices remaining flat. This satisfies existing shareholders anddraws new ones, driving up the stock price. There are two types of dividend payments that some firmsmake annual dividends and quarterly dividends. Consequently, if a company has a history ofannouncing large dividends, you should buy its stock upon hearing of an impending dividendannouncement because you will not only receive the dividend (“by simply paying the share price duringthe purchase”), but you will also likely benefit from capital appreciation in the near future. Last but notleast, dividends are an indication of financial health and growth for a corporation.